DAMPAK LINGKUNGAN HIDUP DARI USAHA PETERNAKAN AYAM DAN AKIBAT HUKUMNYA DI DESA CANDIREJO MOJOTENGAH WONOSOBO - Andi Purnama; Rochmani Rochmani (Fakultas Hukum Universitas Stikubank, 2017)
Chicken Ranch venture is a business that is environmentally friendly and efficient, the management of maintenance, cage, and the handling of waste should always be considered. But the farm that stood in the village of Wonosobo Mojotengah Candirejo not in accordance with the applicable rules on the farm, a location close to settlements and ignore the handling of waste and effort. .This Method approach used in this study is the sociological juridical approach. To approach the problem in this study the author uses descriptive analytical research specifications. The collection of data through primary data and secondary data. Methods of presenting data in research conducted in a descriptive way. The analysis used in this thesis is qualitative. The results showed that (1) Overview of the Business Environment Poultry in the village of Wonosobo Mojotengah Candirejo terms of Environmental Aspects, regulated by Law No. Law No. 41 of 2014 concerning Animal Husbandry and Animal Health and Licensing Guidance And Business Registration Ranch, which states that the livestock company and certain parties who seek cattle to scale certain businesses are obliged to follow the procedures for aquaculture animals is not well with disturbing public order in accordance with the guidelines set by the minister in addition to the licensing process must be approved by the farm community about the location where the livestock business to be established. (2) An environmental impact arising from the chicken farm that is a negative impact in the form of environmental pollution, odor, chicken health while the positive impact chicken farm can boost the empowerment of local communities. Thus in maintaining farm Candirejo Mojotengah Wonosobo should implement procedures Efforts Environmental Sustainability and Environmental Monitoring Effort (UKL / UPL) if the procedure Efforts Environmental Sustainability and Environmental Monitoring Effort (UKL / UPL) is not implemented then it will be penalized environmental law in this case will be in wear business license revoked.